An Industrial DAQs and Internet Based Data Logging and Remote Monitoring System for Real-Time Multi-Parameters Measurements - Thang, Tran Vinh; Kien, Do Trung (VNU Journal of Science: Mathematics - Physics, 2014)
Abstract: In this paper, we proposed a design and implementation of a multi-parameters data logging and remote monitoring system for investigating both of electrical parameters and physical ones for indoor and outdoor environments. The task of logging and monitoring parameters are temperature, relativity light intensity and nineteen electrical parameters with storage and transmission of this information in the form cloud storage service to the user’s computer over internet in real-time for in-situ or further analysis. Due to industrial data acquisition modules, this system is easy to build with an expandable capability and enduring stability. Also a large of logged data can be measured by using this system with high accuracy and they are able to observe in a large surveying area. Keywords: DAQ-data acquisition, data logger, remote monitoring system.